Enhancing the ability to write poetry and creative thinking skills with rural nature-inspired contextual approach - Maria Goreti Rini Kristiantari; I Wayan Widiana; Gde Artawan (International Journal of Evaluation and Research in Education (IJERE), 2023)
There are still many students who face difficulty in expressing ideas for writing poetry, and not a few students are less motivated in writing literary works in the kind of poetry. The aim of this study was to analyze the effect of learning with a rural nature-inspired contextual approach on the ability to write poetry and creative thinking skills of elementary school students. Quasi-experimental study is used in this study with a non-equivalent pre-test post-test control group design. The research population was all fifth-grade students, totaling 231 students. The sample was taken by random sampling technique, totaling 44 students. Data were collected using a test technique. The test instruments were in the form of a description test and a five-scale non-test instrument. Both instruments have been analyzed for their feasibility quality by testing their validity and reliability. The data analysis technique used MANOVA with the help of SPSS. The results showed that the significance value of the MANOVA test results was 0.000 (<0.0). It means that there is a difference in both partial and simultaneous studies in writing poetry and students’ creative thinking skills who learn by applying a contextual approach inspired by rural nature. So, there is a positive effect of learning with a rural nature-inspired contextual approach on the ability to write poetry and creative thinking skills.